Analysis of the Nano-composite Column using Static and Dynamic Methods - Goh, Ching Pang; Tan, Weng Chun (INTI International University, 2023)
A nano-composite is a multi-phase material characterised by its size, which is typically smaller than 100 nanometers. The material is formed by repeating distances between the phases. The material has garnered significant attention from researchers worldwide because to its superior mechanical, physical, and biological qualities in comparison to traditional composite materials. Nano-composites have been employed in the fabrication of aerospace vehicle components, such as wings, tails, and propellers, as well as high-performance racing car bodies, owing to their exceptional durability and lightweight characteristics. The primary goal of this research is to do both static and dynamic analysis on a nano-composite column composed of metal, ceramic, and polymer matrix nano-composites. The ANSYS simulation software will be utilised to analyse the deformation and equivalent (von-Mises) stress. The simulated analysis would employ compressive force. In addition, the nano-composite column will be examined under 4 distinct boundary conditions to demonstrate how it deflects in response to compressive force. This research aims to investigate the possibilities of nano-composite materials and their potential for effective utilisation in the near future